COMMENTS TO THE ARTICLE BY S.V. BUDALINA, S.A. TSAR'KOVA, V.P. SHILOVA «MEANING OF IMMUNIZATION BY PNEUMO 23 AND ACT HIB IN THE PREVENTION OF THE RECURRENT RESPIRATORY DISEASES IN CHILDREN FROM THE CLOSED CHILDREN'S FACILITIES» - V.К. Tatochenko (Union of pediatricians of Russia, 2007)
.